The S-Word Addressed: Estimating Age from Human Skeletal Remains - Dabbs, Gretchen R..
The idea that accurate age estimation based on the analysis of human skeletal remains is not possible has become somewhat proliferate among Egyptologists in recent years, stemming from Dodson’s presentation of the scientifically questionable results of the Spitalfields archaeology project. This article identifies several scientific miscues in the Spitalfields project, including: (1) observer and confirmation bias; (2) deviation from the published methods for age estimation; and (3) expecting a degree of precision not possible in skeletal age estimations. In doing this, the authors hope to clarify that any conclusion that age estimation based on skeletal analysis is not fruitful based on the Spitalfields project is unsound. Additionally, evidence is presented from other authors that demonstrate skeletal age estimation is accurate, including work performed on the Spitalfields sample.